Managing patient safety and quality of care in public hospitals in Pakistan - Rehman, Adeela; Mohamad Diah, Nurazzura (Future Academy, 2017)
The provision of confined and renowned care to the patients is the most important concern of hospitals, in line with patients’ privilege and rights. It is the state’s primary responsibility to provide all types of free healthcare services to the population, particularly maternal healthcare, on a priority basis. In this regard, public hospitals are playing a crucial role in provisioning quality healthcare services to all. This study explores public hospitals’ performances to provide maternal healthcare services to the general population. Based on the qualitative research paradigm, interviews were conducted among patients, doctors and staff/nurses to know their perception and experiences of maternity healthcare services at public hospitals. The findings indicated that public hospitals have a separate unit for maternal healthcare and are doing their best to provide safe and quality healthcare services to mothers and newborns with limited resources. Meanwhile, although various types of services are provided by the caregivers, work overloads and lack of space make patients feel unsatisfied with the quality of their services. The study concluded that quality of care is the major concern of the hospitals besides the lack of monitoring and accountability of resources utilization. In this light, patients feel deprived of rightful services they wish to attain from the hospitals. Improving on-job training and physical resources are recommended to enhance the provision of quality healthcare services to mothers and newborns.